Media’s Multilingual Shift: Assessing The Impact of Unofficial Languages On Tanzania’s Linguistic Landscape - Haule, j, Emmanuely; Mhagama, Willy; Wang'uba , Joel; Nsyengula, P., Stephen (English Lecturers and Teachers Association (ELTA), 2024)
This study explored the impact of Arabic and Asian languages in Tanzanian mass media on the growth and status of the country's official languages, Swahili and English. The primary aim was to evaluate how multilingual football commentaries, particularly on Azam Television and Tanzania Broadcasting Corporation (TBC), influenced the linguistic landscape of Tanzania. Employing an exploratory qualitative research design, data were collected through semi-structured interviews and documentary reviews involving 15 participants, including media reporters, a representative from the Ministry of Culture, and citizens from Mbeya City. The findings indicated that while the use of non-official languages enriched cultural experiences and promoted linguistic diversity, it also posed significant challenges to the prominence and growth of Swahili and English, and could marginalize vernacular languages. The study recommended a nuanced media language policy that promotes linguistic diversity while safeguarding the integrity of official and indigenous languages, along with strategic investments to support high-quality multilingual content without imposing financial burdens on media organizations. Keywords: Multilingual Media, Language Growth, Swahili and English, Linguistic Diversity